MicroRNA-27a-3p enhances the inflammatory phenotype of Juvenile Idiopathic Arthritis fibroblast-like synoviocytes - Claire H. Bullock; Sarah M. McAlpine; Sarah E. Roberts; Beata Derfalvi (BMC, 2023)
Abstract Background Juvenile Idiopathic Arthritis (JIA) is the most prevalent chronic pediatric rheumatic disorder. In joints of JIA patients, aggressive phenotypic changes in fibroblast-like synoviocytes (FLS) of the synovial lining play a key role in inflammation. MicroRNAs are dysregulated in rheumatoid arthritis and JIA, including miR-27a-3p. However, it is not understood if miR-27a-3p, enriched in JIA synovial fluid (SF) and leukocytes, alters FLS function. Methods Primary JIA FLS cells were transfected with a miR-27a-3p mimic or a negative control microRNA (miR-NC) and stimulated with pooled JIA SF or inflammatory cytokines. Viability and apoptosis were analyzed by flow cytometry. Proliferation was evaluated using a 3H-thymidine incorporation assay. Cytokine production was assessed by qPCR and ELISA. Expression of TGF-β pathway genes was determined using a qPCR array. Results MiR-27a-3p was constitutively expressed in FLS. Overexpression of miR-27a-3p caused increased interleukin-8 secretion in resting FLS, and interleukin-6 was elevated in SF-activated FLS compared to miR-NC. Furthermore, stimulation with pro-inflammatory cytokines augmented FLS proliferation in miR-27a-3p-transfected FLS relative to miR-NC. Expression of multiple TGF-β pathway genes was modulated by overexpression of miR-27a-3p. Conclusions MiR-27a-3p significantly contributes to FLS proliferation and cytokine production, making it a potential candidate for epigenetic therapy that targets FLS in arthritis.